Diagnostic Approach in Isolated Bulbar Amyotrophic Lateral Sclerosis: A Case Report - Nunung Nugroho; Albert Setiawan (Indonesian Journal of Physical Medicine & Rehabilitation, 2021)
ABSTRACTIntroduction: Amyotrophic lateral sclerosis (ALS) is the most common motor neuron disease. Based on the clinical manifestation, it is divided into spinal form and bulbar form. Bulbar form ALS is divided into two, progressive bulbar and isolated bulbar ALS (IBALS). Patients are diagnosed with IBALS whensymptoms are isolated in the bulbar region for at least six months. The prevalence of IBALS represents only 4% of the neuron disease.Objective: To provide the diagnostic approach of IBALS case based on the clinical signs and symptoms, physical examination, laboratory and radiology findings, electromyography, and fiber optic laryngoscopy examination.Case: A 64-year-old woman presented with slurred speech, the symptoms appeared 2 years ago. Within the last 6 months, the symptoms deteriorated, the patient was unable to speak, and had major difficulty in swallowing food and drinks. The functional status impairment was limited in the bulbar region.Laboratory and radiology findings did not lead to any certain disease. Electromyography and fiber optic laryngoscopy results suggesting a motor neuron disease.Conclusion: It is important to diagnose ALS patients to determine the treatment, progressivity, and prognosis of the disease.Keywords: amyotrophic lateral sclerosis, bulbar form, diagnosis